EP Elections as a Tool for Migrant Political Participation - Małgorzata Kułakowska (Ksiegarnia Akademicka Publishing, 2019)
The paper focuses on the European Parliament (EP) elections seen as a tool for migrant political participation. When migrating for work, EU migrants do not always consider naturalization as an optimal arrangement, being satisfied with rights connected with their EU citizenship. Therefore, in terms of voting strategies, they often limit their voting rights to those connected with the institutions of their country of birth. However, the particular political context might create additional motivation for participation in EP elections. I would argue that such a particular situation did occur in the United Kingdom in May 2019, when many EU migrants decided to exercise their right to vote in EP elections. Furthermore, many of them were then denied this right, which has been attributed by some to the lack of efficiency on part of British institutions. The paper will look at the institution of the European Parliament elections, analyzing both the normative justification of the formal arrangements and the empirical dimension of 2019 EP Elections in the United Kingdom in the context of the ongoing processes of Brexit.